2013
DOI: 10.3109/10253890.2013.816841
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress is associated with anxiety, increased stress responsivity and preference for “comfort foods” in adult female rats

Abstract: Chronic stress increases anxiety and encourages intake of palatable foods as "comfort foods". This effect seems to be mediated by altered function of the hypothalamic-pituitary-adrenal axis. In the current study, litters of Wistar rats were subjected to limited access to nesting material (Early-Life Stress group - ELS) or standard care (Control group) from postnatal day 2 to 9. In adult life, anxiety was assessed using the novelty-suppressed feeding test (NSFT), and acute stress responsivity by measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 43 publications
5
47
0
Order By: Relevance
“…The consequences of early-life (prenatal as well as postnatal) stress on emotional and social behaviors have been a subject of several recent reviews (eg, Sandi and Haller, 2015;Nishi et al, 2014). Here, we summarize in Table form the consequences of chronic early-life adversity provoked by abnormal maternal care in the limited bedding-nesting environment (Gilles et al, 1996;Molet et al, 2014), a model recently adopted and adapted by over 50 laboratories around the world (eg, Raineki et al, 2010;Wang et al, 2011;Bolton et al, 2013;Machado et al, 2013;Maniam et al, 2014;Kohl et al, 2015;Naninck et al, 2015; Table 1). …”
Section: Emotional and Social Consequences Of Early-life Experience Vmentioning
confidence: 99%
“…The consequences of early-life (prenatal as well as postnatal) stress on emotional and social behaviors have been a subject of several recent reviews (eg, Sandi and Haller, 2015;Nishi et al, 2014). Here, we summarize in Table form the consequences of chronic early-life adversity provoked by abnormal maternal care in the limited bedding-nesting environment (Gilles et al, 1996;Molet et al, 2014), a model recently adopted and adapted by over 50 laboratories around the world (eg, Raineki et al, 2010;Wang et al, 2011;Bolton et al, 2013;Machado et al, 2013;Maniam et al, 2014;Kohl et al, 2015;Naninck et al, 2015; Table 1). …”
Section: Emotional and Social Consequences Of Early-life Experience Vmentioning
confidence: 99%
“…For example, chronic and strong stress induced decrease of food intake and loss of body weight [14], whereas mild stress increased food intake, especially that of highly palatable foods [15][16][17][18]. It is also reported that stress strongly modified ileal motility and that there were sex differences in the effects of stress-loading [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Both diets were produced by the Prag Soluções Biociências  Laboratory (São Paulo, Brazil), aiming to minimize possible biases. Data from food intake can be found in another publication 1 .…”
Section: Subdivision Of Neonatal Groups In Different Dietsmentioning
confidence: 99%
“…Exposure to early-life trauma leads to behavioral changes in adulthood 1,2 as well as to changes in the functioning of the hypothalamic pituitary adrenal (HPA) axis mediated by alterations in maternal care 1 . By observing the natural variations of maternal care in rats, researchers have classified dams as high-and low-caring mothers.…”
mentioning
confidence: 99%